UJI DAYA TERIMA DAN KANDUNGAN GIZI KUE PAO MODIFIKASI BERBAHAN MOCAF, BIT DAN KOLANG KALING (ANALYSISOF THE ACCEPTABILITY AND THE NUTRIENTS OF MODIFIED PAO WITH THE INGREDIENTS ARE MOCAF, BEET AND THE FRUIT OF SUGAR PALM) - Siti Ardianti A Panjaitan; Zulhaida Lubis; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
This research had backgrounds were the food diversification and the food functional that could be applied in producing modified pao with the ingredients were mocaf, beet and the fruit of sugar palm. The food diversification was applied by using mocaf as the substitution matter of wheat to make the pao based on local food whereas the food functional was applied by using beet and the fruit of sugar palm as the ingredients to make the filling of the pao. This research purposed to get the acceptability and the nutrients contens of the pao. The kind of this research was experiment with random complete designing with two factors were mocaf and wheat with two treatments were using comparation 30 : 70 and 40 : 60. The acceptability test has been done by the organoleptic analysis involed 30 panelists and then the result were analysed by the descriptive percentage. This research also had the nutrient analysis as The SNI 01-2891-1992 standart. The acceptability of the pao in the comparation 30:70 treatment was liked in color, scent, taste and texture whereas the comparation 40:60 treatment also was liked in color, scent and taste but not so liked in texture. The T-Independent Test by using the SPSS aplication proved that there was not difference of acceptability between the 30% mocaf in pao and the 40% mocaf in pao. It meant that the acceptability of both paos are same good. The nutrient analysis result showed that the 30:70 pao’s treatment had the total calorie was 66 Calories and the 40:60 pao’s treatment had 70 Calories. The result of this research showed that panelists liked both two treatments of Modified Pao. As to the nutrient analysis, the pao (30gr) could be snack contened about 3 % of a total of calori based on avarege needs of adultsin age 19-29 between 2250 to 2750 Calories need a day (based on The Number of Daily Energi Intake 2013) . It is suggested to do the further research than this research that concern on the micro nutrient. Key words : The Acceptability, The Pao, Mocaf, Beet, The Fruit of Sugar Palm